The Adsorption Capacity of Platelets - Dóczy, A; Fejér, A (Thrombosis and Haemostasis, 1963)
Thrombocytes stored at 37° C were suspended in fresh normal plasma free of platelets. Then the behaviour of the thrombocyte factors 1, 2 and 3 was investigated. It was found that the activity of factor 3 did practically not change during the experiments whereas the thrombocytes adsorbed the factor 1, and 2 and regained the normal activity.